DESIGN ELEMENTS OF THE AUTOMATED CONTROL SYSTEMS PRODUCTION ENTERPRISES AVIATION INSTRUMEN - P. P. Dobrov (Модернизация, инновация, развитие)
There are considered the basics of organization of design of the automated  enterprise control systems elements of the aircraft instrument engineering enterprises; there are specified the stages of introduction of the AECS of the aircraft instrument engineering enterprises; there are considered the aspects of choice of means and tools of the enterprise automation. There is specified that it is very important to clearly define the goals, objectives and methods of automation, to take into account the economic component  of design and implementation, and regulatory requirements for automation upon organization of design of the AECS elements of the aircraft instrument engineering enterprises. These requirements are recommended to be reflected in the design technical specification and in the business plan of automation, which is an organizational and economic design tool. An important element of the business plan of automation shall be a financial justification, cost calculation and determination of the schedule of scientific-research and development works, and other important stages of design of the AECS elements. It was found that the most effective approach to the organization of design of the AECS elements from an economic and organizational point of view is the cooperation of engineering and IT departments of enterprises and technical professionals (units) of third-party developers. It was determined that an important technology to optimize the design process is the application of the integrated automation design systems. The recommendations can form the basis of the process of improving of design of the automated enterprise control systems elements at domestic and foreign aircraft instrument engineering enterprises.